The Spiritual Health Services in the Face of the COVID-19 Pandemic: A Hybrid Study - Asadzandi, Minoo; Abolghasemi, Hasan (Journal of Patient Care and Services, 2021)
Background COVID-19 as an infectious disease, and deadly biological crisis, threatens the bio-psycho-social- spiritual health of the people. Spiritual health from the perspective of Islam, means having a sound heart, living in the present time with sense of peace, security, patience and gratitude, safe from the fear and anxiety of future, grief and regret for the past events. It affects other dimension of health. This study was conducted to investigate the spiritual health services in the face of the COVID-19 pandemic in a Muslim society. Methods This qualitative study was conducted from March 1, 2020 to the end of May 2020 in Tehran by using the Schwartz and Kim's hybrid model concept analysis with a deductive / inductive analysis approach, in three stages: 1- Theoretical review of religious and scientific evidence, 2- Field research 3- Final analysis. Data collection was done in hospitals and hospices by semi-structured interviews, taking notes, websites and social networks search. Data were analyzed by "Contractual Content Analysis Method". Results Despite the fact that spiritual health services (spiritual care and counseling) are not taught in Iranian universities, but in this biological crisis, spiritual health services, based on religious beliefs of health system employees were implemented. The Muslims’ belief in divine test, healing power of God, helping the people as highest worship, aroused spiritual awakening and enthusiasm in the health care team. Spiritual health services at prevention levels were provided with the aim of helping the patient, family and clients, in an inter-professional model based on the jurisprudential rules derived from the religious evidences (Verses and Hadiths), in line with holistic approach, community-based care, spiritual self-care, home-care, family participation. The involvement of non-specialists in the provision of medical services was prevented. According to, preserving the human dignity in Islam, Islamic rituals were performed by the treatment team and volunteer clerics for dying and dead people. Conclusion Considering the impact of religious spirituality on Muslims’ lifestyle and health behaviors, it seems that the use of Islamic health guidelines can improve the quality of health care services and help improve the spiritual health of people in biological crises.
Keywords: COVID-19; Spirituality; Health; Inter-professional